Genetic Diversity Linked to Haplotype Variation in the World Core Collection of Trifolium subterraneum for Boron Toxicity Tolerance Provides Valuable Markers for Pasture Breeding - Tahghighi, Hediyeh; Erskine, William; Bennett, Richard G.; Bayer, Philipp E.; Pazos-Navarro, Maria; Kaur, Parwinder (Frontiers in Plant Science, 2019)
In alkaline soils in arid and semi-arid areas toxic concentrations of the micronutrient boron (B) are problematic for many cereal and legume crops. Molecular markers have been developed for B toxicity in cereals and Medicago. There is a need for such tools in clovers – Trifolium. To this end we undertook a genome-wide association study (GWAS) with a diversity panel of subterranean clover (Trifolium subterraneum L.), an established model pasture legume for genetic and genomic analyses for the genus. The panel comprised 124 T. subterraneum genotypes (97 core collection accessions and 27 Australian cultivars). Substantial and useful diversity in B toxicity tolerance was found in T. subterraneum. Such variation was continuously distributed and exhibited a high broadsense heritability H2 = 0.92. Among the subspecies of T. subterraneum, ssp. brachycalycinum was most susceptible to B toxicity (P<0.05). From the GWAS the most important discoveries were Single Nucleotide Polymorphisms (SNPs) located on Chr 1, 2 and 3 which mapped to haplotype blocks providing potential genes for a B toxicity tolerance assay and meriting further inverstigation. A SNP identified on Chr 1 aligned with Medicago truncatula respiratory burst oxidase-like protein (TSub_ g2235). This protein is known to respond to abiotic and biotic stimuli. The identification of these novel potential genes and their use to design markers for marker-assisted selection offer a pathway in pasture legumes to manage B toxicity by exploiting B tolerance.